Vascular Air Embolism in Neonates: A Literature Review - Zhou, Qi; Lee, Shoo K. (American Journal of Perinatology, 2025)
Neonatal vascular air embolism is a rare but often fatal condition. The literature comprises mostly case reports and a few dated systematic reviews. Our objective was to review all case reports of neonatal vascular air embolism to date and provide up-to-date information about patient characteristics, clinical presentations, outcomes, pathogenesis, diagnosis, prevention, treatment, and prognosis. We searched the literature for case reports of neonatal vascular air embolism, using MEDLINE, CINAHL, and EMBASE, and the keywords “neonates” and “vascular air embolism.” Results were summarized. There were 117 cases of neonatal vascular air embolism, with a mean gestational age of 30.4 weeks (range: 23–40), mean birth weight of 1,422 g (range 830–3,844), and median age of occurrence of 2 days (range: 1–540) after birth. The majority were preterm (75.2%), male (62.7%), on assisted respiratory support (90.5%), and had air leak syndrome (52.9%). The most common clinical presentation was sudden acute clinical deterioration, sometimes accompanied by crying, cardiac rhythm abnormalities, skin discoloration, and a decrease in end-tidal carbon dioxide concentration. Incidence of mortality and adverse neurological sequelae among survivors was 73.9 and 16.6%, respectively, overall, but significantly (p < 0.05) higher among preterm infants (81.8 and 31.2%, respectively) and lower among surgical infants (23.8 and 0%, respectively). Diagnosis included visualizing air in infusion lines or retinal vessels, a decrease in the end-tidal carbon dioxide levels, and radiographic, doppler ultrasound, transesophageal echocardiography, or computed tomography (CT) imaging. The prognosis for neonatal air embolism is poor, especially for preterm infants requiring mechanical ventilation. Prevention is key and treatment is supportive.
Keywords: vascular air embolism; neonates; preterm infants